Managers attitude towards implementing workplace health promotion programmes to employees in eldercare: a cross-sectional study - J.R. Christensen; C.M. Larsen; M.I. Kolind (Elsevier, 2020)
Objectives: To determine the attitudes of eldercare services managers to the potential health benefits of workplace health promotion programmes (WHPPs), including physical exercise during working hours and the feasibility of implementing a WHPP at the workplace. Study design: A cross-sectional study. Methods: Respondents filled out a 14-item questionnaire on attitudes towards the potential health benefits of WHPPs and the feasibility of implementing WHPPs. Differences between groups were analysed using the Kruskal-Wallis test. The significance level was set to p ​= ​0.05. Bonferroni's correction was used in the setting of multiple comparisons. A content analysis was performed exploring answers provided in the optional comment section in the questionnaire. Results: 695 eldercare services managers in Denmark were contacted by email, 393 replied, and 382 respondents were included in the analysis (54.7%). The survey revealed that 89.8% of the respondents believed that WHPPs would increase health, 89.6% believed that it would increase well-being and 87.6% believed that WHPPs would increase workability among workers. 87.7% expressed a willingness towards implementing WHPPs and believed 'it to be a good idea'. Respondents with a negative attitude to the feasibility of implementing WHPPs, were more likely to hold negative attitudes to the potential health benefits of WHPPs (p ​< ​0.001). Organisational issues were the most frequently stated barrier to implementation. Conclusions: The majority of eldercare managers expressed a positive attitude to the benefits of WHPPs and their implementation. Addressing organisational issues and ensuring management support in the planning stage of a WHPP is highly important.